KETERWAKILAN PEREMPUAN DI DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN TANAH DATAR PERIODE 2014-2019 - Irmalinda, Zikra Putri; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The women representative in Indonesia politics became an inevitable thing for political parties, when the General Election Commissions (KPU) issued PKPU regulation No.13/2013. Women's representative in Tanah Datar Regency which initially faced some obstacles, they were Minangkabau culture or women themselves and external constraints. The core problem on political representation in Tanah Datar Regency was women's political enthusiasm still low to participate in politics than men. It was influenced by Minangkabau culture. It was evidenced by the fact that there were still a few women who hold public positions and were able to play an active role in political life. Through interviews the informants who were leaders and women legislative members in the 2014 Regional People's Court Council (DPRD) elections, has provided an overview of the struggle of women become members of the Regional People's Court Council (DPRD) in Tanah Datar Regency.This study purposed to describe the representation of women in the Tanah Datar regency parliament in 2014-2019. This study used a qualitative approach Setting of the reseach in Tanah Datar regency West Sumatra province. The sources of data were interviews, documents, and printed media. The techniques of data collection used interview and documentation. The data was analysised by qualitative analysis with the type of  descriptive.The conclusion from this research showed that the representative of women in Tanah Datar regency especially in Minangkabau women were still low and has difficult access to politics than men. The inhibiting factors that influence the representation of women in the Tanah Datar regency legislative council were women's competence in politics, recruitment systems, cultural and religious factors, agency factor, internal and external factors. The women who had a family background of officials and were active in community organization were a very favorable political modality for women to be elected in the Tanah Datar Regional people's court council (DPRD).   Keywords: women's politics, elections and legislatures.